Pharmacologic Management of Mycobacterium chimaera Infections: A Primer for Clinicians. (15th June 2022) - Mason, Matt; Gregory, Eric; Foster, Keith; Klatt, Megan; Zoubek, Sara; Eid, Albert J
Abstract: Mycobacterium chimaera, a member of the Mycobacterium avium complex, can cause infections in individuals after open heart surgery due to contaminated heater-cooler units. The diagnosis can be challenging, as the incubation period can be quite variable, and symptoms are nonspecific. In addition to aggressive surgical management, combination pharmacologic therapy is the cornerstone of therapy, which should consist of a macrolide, a rifamycin, ethambutol, and amikacin. Multiple second-line agents may be utilized in the setting of intolerances or toxicities. In vitro susceptibility of these agents is similar to activity against other species in the Mycobacterium avium complex. Drug–drug interactions are frequently encountered, as many individuals have chronic medical comorbidities and are prescribed medications that interact with the first-line agents used to treat M. chimaera . Recognition of these drug–drug interactions and appropriate management are essential for optimizing treatment outcomes.